Testing the Effect of Using English Vocabulary Profile Platform on the Improvement of EFL Learners’ Vocabulary Case of First year LMD Students of Mohamed Cherif Messaadia University, Souk-Ahras - Manel BEN AOUADJ (My University, 2024)
ABSTRACT This study examines the effectiveness of the English Vocabulary Profile Platform on improving first year students’ vocabulary skills, in the department of English language at Mohamed Cherif Messaadia, in Souk-Ahras. The English Vocabulary Profile is an interactive resource which is not commonly used in the Algerian learning and teaching. This study was conducted using a mixed method approach to collect both qualitative and quantitative data. Two main instruments had been utilized. First of all a pre experimental design is adopted and the study is carried out during the academic year 2023/2024 on 32 students, which randomly selected from 206 first year student. Two main instruments had been utilized. Pre-experiment questionnaire composed of 13 questions was administered to all students. Secondly, an experiment with the same sample was conducted, over the course of 07 sessions, beginning on Sunday, Mach 03, 2024, and finishing on Sunday April 17, 2024. The findings of the study show that by incorporating the English Vocabulary Profile platform into their learning, students exhibit a notable improvement in their vocabulary skills. Based on this result, the study offers recommendations and suggestions areas for further research. -------------- ملخص تهدف هذه الدراسة إلى فحص فعالية منصة ملف الكلمات الإنجليزية في تحسين مهارات المفردات لطلاب السنة الأولى في قسم اللغة الإنجليزية بجامعة محمد شريف مسا عدية في سوق أهراس. منصة ملف الكلمات الإنجليزية هي مورد تفاعلي غير معتاد عليه في التعلم والتدريس في الجزائر. تمت الدراسة باستخدام نهج مختلط لجمع البيانات النوعية والكمية. تم استخدام أداة رئيسية واحدة. أولاً، تم اعتماد تصميم قبل التجريب وأُجريت الدراسة خلال السنة الأكاديمية 2024/2023على 32طالبًا، تم اختيارهم عشوائيًا من بين 206طالبًا في السنة الأولى. ثم تم توزيع استبيان قبل التجريب مكون من 13سؤا ًلا على جميع الطلاب. ثانياً، تم إجراء تجربة مع نفس العينة على مدار 07جلسات، بدءاً من يوم الأحد، 03مارس ،2024وانتهاء في يوم الأحد 17أبريل .2024أظهرت نتائج الدراسة أنه من خلال دمج منصة ملف الكلمات الإنجليزية في عملية تعلمهم، يبدي الطلاب تحسي ًنا ملحو ًظا في مهارات المفردات لديهم. استنادًا إلى هذه النتائج، تقدم الدراسة توصيات واقتراحات لمجالات بحثية مستقبلية. -------------------- Résumé Cette étude examine l’efficacité de la plateforme profile vocabulaire anglais sur l’amélioration des compétences en vocabulaire des étudiants de première année du département de langue anglais à Mohamed Cherif Messaadia, à Souk-Ahras. Le profil vocabulaire anglais est une ressource interactive qui n’pas couramment utilisée dans l’apprentissage et l’enseignement en Algérie. Cette étude a été menée en utilisant une approche mixte pour collecter des données qualitatives et quantitatives. Deux principaux instruments ont été utilisés. Tout d’abord, un plan pré-expérimental a été adopté et l’étude a été menée pendant l’année académique 2023/2024 sur 32 étudiants, choisis de manière aléatoire parmi les 206 étudiants de première année. Deux principaux instruments ont été utilisés. Un questionnaire pré-expérimental composé de 13 questions a été administré à tous les étudiants. Deuxièmement, une expérience avec le même échantillon a été menée, sur une période de 07 sessions. Débutant le dimanche 03 mars 2024 et se terminant le dimanche 17 avril 2024. Les résultats de l’étude montrent qu’en intégrant la plateforme profile vocabulaire d’anglais dans leur apprentissage, les étudiants présentent une amélioration notable de leurs compétences en vocabulaire. Sur la base de ces résultats, l’étude propose des recommandations et des suggestions pour des domaines de recherche ultérieurs.